Eye movements and stress during eye‐tracking gaming performance in children with dyskinetic cerebral palsy. (8th April 2022) - Bekteshi, Saranda; Karlsson, Petra; De Reyck, Lieselot; Vermeerbergen, Karen; Konings, Marco; Hellin, Patrick; Aerts, Jean‐Marie; Hallez, Hans; Dan, Bernard; Monbaliu, Elegast
Abstract: Aim: This study aimed to explore eye movements and stress during eye‐tracking gaming performance in children with dyskinetic cerebral palsy (CP) compared with typically developing children, and associations between eye‐tracking performance, eye movements, stress, and participants' characteristics. Method: This cohort study included 12 children with dyskinetic CP aged 5 to 12 years (mean age 8 years 7 months, standard deviation [SD] 2 years 3 months) and 23 typically developing children aged 5 to 13 years (mean age 9 years 0 months, SD 2 years 7 months). Participants played 10 eye‐tracking games. Tobii X3‐120 and Tobii Pro Lab were used to record and analyse eye movements. Stress was assessed through heart rate variability (HRV), recorded during rest, and eye‐tracking performance using the Bittium Faros360° ECG Holter device. Eye‐tracking performance was measured using gaming completion time. Fixation and saccade variables were used to quantify eye movements, and time‐ and frequency‐domain variables to quantify HRV. Non‐parametric statistics were used. Results: Gaming completion time was significantly different ( p < 0.001) between groups, and it was negatively correlated with experience ( r s = −0.63, p = 0.029). No significant differences were found between groups in fixation and saccade variables. HRV significantly changed from rest to eye‐tracking performance only in typically developing children and not in children with dyskinetic CP. Interpretation: Children with dyskinetic CP took longer to perform the 10 games, especially the inexperienced users, indicating the importance of the early provision of eye‐tracking training opportunities. It seems that eye‐tracking tasks are not a source of increased stress and effort in children with dyskinetic CP. What this paper adds: Participants with dyskinetic cerebral palsy (CP) took twice as long to perform 10 eye‐tracking games than typically developing peers. Participants with dyskinetic CP with previous eye‐tracking experience performed the games faster. Fixation and saccade variables were not significantly different between children with and without dyskinetic CP. Heart rate variability showed no differences between rest and performance in participants with dyskinetic CP. Gross Motor Function Classification System, Manual Ability Classification System, and Viking Speech Scale levels were not correlated to the eye movements or stress variables. What this paper adds: Participants with dyskinetic cerebral palsy (CP) took twice as long to perform 10 eye‐tracking games than typically developing peers. Participants with dyskinetic CP with previous eye‐tracking experience performed the games faster. Fixation and saccade variables were not significantly different between children with and without dyskinetic CP. Heart rate variability showed no differences between rest and performance in participants with dyskinetic CP. Gross Motor Function Classification System, Manual Ability Classification System, and Viking Speech Scale levels were not correlated to the eye movements or stress variables. The majority of children with dyskinetic cerebral palsy rely on eye‐tracking technology for communication and computer access. The eye movements that facilitate this interaction and the ease of use were not explored before. Findings show that the fixation and saccade variables of children with dyskinetic cerebral palsy are not significantly different from the ones of typically developing children. Eye‐tracking technology is not a source of increased effort and stress in children with dyskinetic cerebral palsy. Thereby, this study highlights the importance of early provision of eye‐tracking technology to maximize its benefits in activities of daily living. This original article is commented on by Stadskleiv on pages 1318–1319 of this issue.